Pengaruh Konsentrasi Gula dan Natrium Metabisulfit terhadap Mutu Manisan Nangka Kering(Artocarpus Heterophyllus) - Kaka, Heleria Ambu; Ahmadi, KGS; Rozana, Rozana (Fakultas Pertanian, 2019)
Candied fruit is a products that is processed by adding sugar with the aim of giving it a sweet taste, and preventing the growth of microorganisms (fungi, yeasts, and bacteria), so that it can extend its storage time. The purpose of this study was to obtain the best concentration of sugar and sodium metabisulfite on the quality of candied dry jackfruit. This research used a Factorial Completely Randomized Design, the first factor was the concentration of sugar solution, with 3 levels, namely: 50%, 60%, and 70%. While the second factor was the concentration of sodium metabisulfite solution with 3 levels, namely: 100 ppm, 200 ppm, and 300 ppm. The results showed that the best treatment (60% sugar and sodium metabisulfi 200 ppm) with physicochemical parameters of water content (0.2758%), sugar content (0.0548%), yield (0.1055%) while organoleptic tests were obtained taste (4,1), aroma (3,8), color (3,8), and texture (3,9). Manisan adalah produk yang diolah dengan menambah gula dengan tujuan untuk memberi rasa manis, dan mencegah tumbuhnya mikroorganisme (jamur, khamir, dan bakteri), sehingga dapat memperpanjang daya simpan. Tujuan penelitian ini adalah menganalisis pengaruh konsentrasi gula dan natrium metabisulfit yang terbaik terhadap mutu manisan nangka kering. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) Faktorial, Faktor pertama konsentrasi larutan gula, dengan 3 taraf yaitu : 50%, 60%, dan 70%. Faktor kedua adalah konsentrasi larutan natrium metabisulfit dengan 3 taraf yaitu: 100 ppm, 200 ppm, dan 300 ppm. Hasil penelitian menunjukkan bahwa perlakuan terbaik (gula 60 % dan natrium metabisulfi 200 ppm) dengan parameter fisiko kimia kadar air (0,2758 %), kadar gula (0,0548 %), rendemen (0,1055 %), sementara uji organoleptik diperoleh rasa (4,1), aroma (3,8), warna (3,8), dan tekstur (3,9).